Residual Dentin Thickness of Bifurcated Maxillary Premolars Following Two Post Space Preparation Methods - Ghoddusi, Jamileh; Forghani, Maryam; Bagherpour, Ali; Mahmudabadi, Fatemeh; Sarmad, Majid (Iranian Endodontic Journal, 2013)
Introduction: The aim of this in vitro study was to compare the effect of Gates-Glidden and Peeso reamer drills on residual dentin thickness during post space preparation in order to discover which method has minimum root structure damage. Materials and Methods: Thirty extracted human maxillary premolars with bifurcations at root middle were horizontally cut 15 mm coronal to the apical end after root canal treatment. The samples were scannedby Cone Beam Computed Tomography (CBCT) before and after preparing the post space. Residual dentin thicknesses were measured at 4-, 6-, and 8-mm levels from the apex. Data were analyzed using repeated measured ANOVA. Results: Endodontic therapy and post space preparations removed more dentin within the bifurcation of both roots compared to outer dentin. The difference in residual dentin thickness was highly significant regarding stage (before and after post space preparation) in all levels and stage × device in coronal and middle levels (P<.05). This in vitro study emphasizes the minimal dentin width in the buccal root of maxillary premolars, especially near the bifurcation. Conclusion: Lack of adequate residual dentin thickness after post space preparation implies that the use of posts in maxillary first premolars should be limited. When mandatory, it is recommended that post space be prepared with Gates-Glidden drill in the palatal root of maxillary first premolars and use of Peeso reamer be avoided.